Fasting-related hyperbilirubinemia in rats: the effect of decreased intestinal motility - Kotal, P; Vítek, L; Fevery, J (Gastroenterology, 1996)
BACKGROUND & AIMS: Fasting increases serum bilirubin levels in both humans and rats. Because the pathogenesis of fasting hyperbilirubinemia is not fully understood, the effect of fasting on disposition of bile pigments was investigated in rats. METHODS: Bilirubin and urobilinogen were determined in excreta, bile, plasma, and liver tissues of fasted Gunn and Wistar rats. RESULTS: Fasting increased the intestinal transit time of Wistar rats. As a result, the fecal output of bile pigments was decreased by food deprivation. In contrast, the intestinal content of total bile pigments was augmented in both Wistar and Gunn rats. This finding was paralleled by the increase of serum bilirubin concentration in both rat strains. A similar increment of serum bilirubin levels was observed after injection of bilirubin into the cecum of Wistar rats. Furthermore, biliary efflux of bilirubin in Wistar rats was increased after 48 hours of fasting. Intubation of nonabsorbable bulk to fasted Wistar rats prevented the increase of serum bilirubin levels during a 48-hour period of food deprivation. CONCLUSIONS: Fasting decreases intestinal motility and elimination of bile pigments. Accumulation of bilirubin in the intestine during fasting allows enhanced enterohepatic circulation and results in an increased reflux to plasma. This seems to be a major factor involved in fasting-induced hyperbilirubinemia.
Keywords: Fasting; játra; feces; střeva; urobilinogen; hyperbilirubinemie; Intestines; Female; střevní sliznice; analýza rozptylu; Bilirubin; Analysis of Variance; krysa rodu Rattus; Rats, Gunn; zvířata; potkani Wistar; Glutathione Transferase; Urobilinogen; Feces; potkani Gunn; ženské pohlaví; Liver; Rats, Wistar; Male; Hyperbilirubinemia; bilirubin; Rats; omezení příjmu potravy; Animals; gastrointestinální průchod; mužské pohlaví; glutathiontransferasa; Intestinal Mucosa; gastrointestinální motilita; Gastrointestinal Transit; Gastrointestinal Motility